THE ANTITHESIS BETWEEN CIVIL LAW AND ISLAMIC LAW IN A PLURALISTIC SOCIETY - Krishnan, Loganathan (Jurnal Syariah, 2010)
Malaysia is known for its pluralistic society. This is because of its multi-racial, multi-cultural and multi-religious society. Thus, the Federal Constitution has been drafted to reflect this spirit. Essentially, one of the Articles of the Federal Constitution provides that Islam is the religion of the Federation and that Islamic law is under the purview of the State. Therefore, State Legislature is responsible for laying down Islamic principles in order to govern the Muslim community. However, there have been occasions where legal issues do arise if one of the contending parties in the courts is not a Muslim. In such a case, the dichotomy is which law should be applied, i.e. Civil Law or Islamic Law. The courts have faced this issue repeatedly in recent years. On such occasions, there have been calls made by various parties to amend the current legal framework to pave the way for the application of Civil Law if one of the contending parties is not a Muslim. However, the government, which is the guardian of the society in totality, has constantly voiced its opinion that these issues will be resolved soon. The purpose of this study is to investigate where the problem lies. The study then proceeds to explore whether there is a way to resolve these issues concerning the application of Civil Law and Islamic Law. Ultimately, society must feel that the outcome takes into account its legal rights and interests for a meaningful pluralistic society.